HUBUNGAN ANTARA BUDAYA PERUSAHAAN DAN KOMITMEN ORGANISASI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA LPP TVRI SUMATERA UTARA - Sunarto Sunarto; Rahmi Lubis (Analitika: Jurnal Magister Psikologi UMA, 2010)
This study aims to meliha Relationship Between Corporate Culture and Organizational Commitment With Organizational Citizenship Behavior (OCB) in North Sumatra TVRI LPP. In line with the theoretical basis of existing, proposed hypotheses: 1. There was a significant positive relationship between Corporate Culture and Organizational Commitment to Organizational Citizenship Behavior (OCBIn proving the above hypothesis, we used regression analysis method of data analysis two predictors. Based on data analysis of the results obtained: 1. There is a significant relationship between corporate culture and organizational commitment on organizational citizenship behavior (OCB). This is evidenced by the coefficient Freg = 1.952 where p <0.050. This indicates that the better the higher the corporate culture and organizational commitment, organizational citizenship behavior then (OCB) will be higher. Instead the worse the lower the corporate culture and organizational commitment, organizational citizenship behavior then (OCB) will be lower as well. Based on these results, the hypothesis proposed been accepted.